The Protection of Religious Freedom under the European Convention on Human Rights - Martínez-Torrón, Javier; Navarro-Valls, Rafael (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1998)
The international protection of the freedom of religion and belief has experienced substantial improvements during the second half of this century. One of the important steps that has been taken by international organizations is the European Convention on Human Rights (1950). The system of the European Convention has often been presented as a model of efficiency in the international protection of human rights, above all for the judicial machinery created to enforce the rights included in the Convention and its Protocols, whose center is the European Court of Human Rights (Strasbourg). The European system, however, is far from perfect, at least as far as the protection of the freedom of religion, conscience and thought is concerned. This article attempts to describe the main strengths and deficiencies of the case-law of the European Court in regard to the freedom of religion and belief. The Court has showed respect for the historical tradition of each country, and has explicitly affirmed that every religious group is entitled to true freedom—not merely toleration. In practice, however, the Court has failed to fully protect the strictly individual dimension of religious liberty, and consequently the rights of some religious minorities seem to be in danger—specially those minorities which defend ideas openly contrasting with the ethical choices assumed by the majority. The article ends with some conclusions on the aspects of the European Court's doctrine that will be advisable to change if it wants to be considered as an example that should be followed in the international environment.